Representasi Humanisme dalam Lirik Lagu Perahu Kertas (Sebuah Kajian Semiotik Roland Barthes) - Afifah Chairunnisa; Silvia Rosa (Universitas Muhammadiyah Jember, 2026)
Songs serve as mirrors reflecting the cultural and philosophical values of their societies. This journal examines how humanism is represented in